2003
DOI: 10.1074/jbc.m210829200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ERK-dependent Signaling Process That Regulates Interleukin-2 Expression in a Late Phase of T Cell Activation

Abstract: Engagement of the T cell antigen receptor (TCR) rapidly induces multiple signal transduction pathways, including ERK activation. Here, we report a critical role for ERK at a late stage of T cell activation. Inhibition of the ERK pathway 2-6 h after the start of TCR stimulation significantly impaired interleukin-2 (IL-2) production, whereas the same treatment during the first 2 h had no effect. ERK inhibition significantly impaired nuclear translocation of c-Rel with a minimum reduction of NF-AT activity. Requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 40 publications
2
71
0
Order By: Relevance
“…Sustained Erk signaling induced by Ag binding to the TCR is required for full activation of T cells and their effector functions, such as IL-2 production (20,22,23). It was reported that B-Raf mediates sustained Erk activation (18)(19)(20), but the molecular mechanism of how stimulation of the TCR is coupled to B-Raf is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustained Erk signaling induced by Ag binding to the TCR is required for full activation of T cells and their effector functions, such as IL-2 production (20,22,23). It was reported that B-Raf mediates sustained Erk activation (18)(19)(20), but the molecular mechanism of how stimulation of the TCR is coupled to B-Raf is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…TCR-induced activation of Raf-1 leads to a transient Erk signal, whereas activation by B-Raf leads to sustained Erk activation in T cells (20,21). Although sustained Erk signaling is crucial for IL-2 production by T cells (20,22,23), it is not understood how TCR triggering leads to B-Raf activation.…”
mentioning
confidence: 99%
“…47 Here we show that ADA-deficient T cells fail to phosphorylate ERKs when exposed to dAdo, indicating that ADA-deficient environment in vivo can directly antagonize biochemical events arising from TCR engagement. Because nuclear translocation of phosphorylated ERKs is required for cytokine production and cellcycle progression, [48][49][50] it is conceivable that dAdo-mediated inhibition of ERKs activation was responsible for the suppressed immune functions in ADA Ϫ/Ϫ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In T cells, upon triggering of the TCR, activation of the MEK/ERK pathway routes signals that are critical for cellular activation, proliferation, and production of cytokines important for the regulation of immune responses (Whitehurst et al, 1992;Karin, 1995;DeSilva et al, 1996;Fields et al, 1996;Li et al, 1996;Alberarola-Ila et al, 1997;Baumgarth et al, 1997). Activation of ERK has been demonstrated to be critical for the proliferation and production of IL-2 in murine primary T cells (Koike et al, 2003). The importance of the JNK cascade in T cell activation and production of IFN-␥ has also been demonstrated (Liu et al, 1997;Yang et al, 1998;Sabapathy et al, 1999;Dong et al, 2000;Behrens et al, 2001).…”
Section: Discussionmentioning
confidence: 97%